Increasing the resolution of ECG and EEG mapping equipment using nanosensors - A. I. Korniyenko; D. K. Avdeyeva; M. M. Yuzhakov; M. L. Ivanov; N. V. Turushev; S. I. Enshin (Омский научный вестник)
The problem of a large number of people with cardiovascular diseases and brain diseases is relevant all over the world. The problem of mortality and the consequences of these diseases is particularly acute. Therefore, an important way in medical instrumentation is to improve and increase the amount of information with the help of external methods of diagnosing these diseases. Nanosensors have been developed at Tomsk Polytechnic University to significantly improve the quality of electrophysiological measurements. It is proposed to apply the developed nanosensors for ECG and EEG mapping.